The Local-Cosmopolitan Scientist - Barney G. Glaser (Grounded Theory Review: An International Journal)
In contrast to previous discussions in the literature treating cosmopolitan and local as two distinct groups of scientists, this paperi demonstrates the notion of cosmopolitan and local as a dual orientation of highly motivated scientists. This dual orientation is derived from institutional motivation, which is a determinant of both high quality basic research and accomplishment of non-research organizational activities. The dual orientation arises in a context of similarity of the institutional goal of science with the goal of the organization; the distinction between groups of locals and cosmopolitans derives from a conflict between two goals.